Changes in industry marketing of electronic nicotine delivery systems on social media following FDA's prioritized enforcement policy: a content analysis of Instagram and Twitter posts - Guillory, Jamie; Trigger, Sarah; Ross, Ashley; Lane, Stephanie; Kim, Annice; Nonnemaker, James; Liu, Sherry T.; Snyder, Kimberly; Delahanty, Janine (Frontiers in Communication, 2023)
Background: In February 2020, FDA prioritized enforcement of flavored (other than tobaccoor menthol-flavored) cartridge-based electronic nicotine delivery systems (ENDS) without premarket authorization. To explore potential marketing changes, we conducted a content analysis of brands' social media posts, comparing devices and flavors before/after the policy. We sampled up to three posts before (November 6, 2019-February 5, 2020) and after the policy (February 6-May 6, 2020) from brands' Instagram (n=33) and Twitter (n=30) accounts (N=302 posts). Two analysts coded posts for device type and flavor. We summarized coded frequencies by device, flavor, and device-flavor combination, and by platform. In posts mentioning devices and flavors, those featuring flavored (other than tobaccoor menthol-flavored) cartridge-based devices (before: 2.5%; after: 0%) or tobacco-or mentholflavored cartridge-based devices (before: 0%; after: 2.8%) were uncommon while any flavor disposables were most common (before: 10.8%; after: 14.6%) particularly after the policy. Half of posts featured devices without flavor (before: 50.0%; after: 50.0%) and one-fifth had no device or flavor references (before: 21.5%; after: 18.8%). In the months before and after the policy, it appears ENDS brands were not using social media to market flavored (excluding tobacco-or menthol-flavored) cartridge-based ENDS (i.e., explicitly prioritized) or tobacco-or menthol-flavored cartridge-based devices (i.e., explicitly not prioritized). Brands were largely not advertising specific flavored products, but rather devices without mentioning flavor (e.g., open/refillable, disposable devices). We presented a snapshot of what consumers saw on social media around the time of the policy, which is important to understanding strategies to reach consumers in an evolving ENDS landscape.